Konsep Pendidikan Agama Islam; Studi atas Pemikiran Ibnu Qayyim Al-Jawziyyah - Moh. Syamsi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2018)
Ibn Qayyim is a Muslim scholar with broad scientific horizons. As a salaf figure, Ibn Qayyim is actually a free researcher who is not bound by madzhab or the opinion of certain scholars except for the truth even though his own teacher, Ibn Taymiyyah. In the perspective of Ibn Qayyim al-Jawziyah Itself Islamic education includes two things namely Tarbiyah Qalb and body education. In addition, Ibn Qayyim also explained that the essence of other Islamic education also includes two things, namely education relating to one's knowledge and education relating to others. The purpose of Ibn Qayyim perspective of Islamic Education is to instill noble morals in students as well as eradicate and combat bad morals from themselves; Creating happiness in him; Always pay attention to it both when they are sleeping and when communicating; Directing how to interact with other humans; Pay attention to clothing so as not to use the prohibited; Directing his talents as well as developing them by giving him tarbiyah diniyah. While the Islamic Education Strategy according to Ibn Qayyim influential from: Al-Manhaj; Adab al-Murabbi and student adab.